Let g(x) = -x2 + x. Find g(-10).

Skip to content# Let g(x) = -x2 + x. Find g(-10).

### Related Posts

##
This Post Has 5 Comments

### Leave a Reply Cancel reply

Home
Mathematics
Let g(x) = -x2 + x. Find g(-10).

Let g(x) = -x2 + x. Find g(-10).

G(x) = -x^2 + x

g(-10) = -(-10)^2 -10

g(-10) = -(100) - 10

g(-10) = -100 - 10

g(-10) = -110

A) is your answer

hope this helps

10

Start by plugging -10 for x.

g(-10)= -(-10)(2) + (-10)

g(-10)=20 + -(10)= 10

A.-110 because itâ€™s -(-10^2) + (-10)

A) [tex]\displaystyle -110[/tex]

Step-by-step explanation:

[tex]\displaystyle -[-10]^2 + -10 = -100 - 10 = -110[/tex]

I am joyous to assist you anytime.

10

Step-by-step explanation: